Isolation and Characterisation of Graves' Disease-Specific Extracellular Vesicles from Tissue Maintained on a Bespoke Microfluidic Device. (1st March 2022) - Green, Victoria; Foster, Hayley; Wade, Mark; England, James; Greenman, John
Abstract: Introduction: Inflammation, a characteristic of Graves' disease, leads to opthalmopathy in 30–50% of Graves' disease patients, and even blindness (5% of cases). Despite extensive research the pathogenesis of this disease remains unclear. This report demonstrates the maintenance of human Graves' disease tissue ex vivo with subsequent isolation and characterisation of Graves' disease specific exosomes. Methods: Human tissue biopsies from Graves' disease (n=11) and non-Graves' disease (Hashimoto's thyroiditis, n=3; follicular adenoma, n=1) were incubated in microfluidic devices for 6 days ± dexamethasone or methimazole, and effluent was analysed for size and concentration of extracellular vesicles (EV) using nanoparticle tracking. Exosomes isolated by ultracentrifugation were characterised using Western blotting and qRT-PCR for miRNA-146a and -155. Results: Tissue specific EV were detected in all effluent samples. No consistent difference in EV concentration or size was observed in EV released from Graves' compared to non-Graves' disease tissue and no effect of treatment was evident. The exosome markers CD63 and CD81 were detectable in 2/5 Graves' disease EV and CD63 was also evident in EV from a single non-Graves' sample. miRNA-146a and -155 were detectable in all samples, with no difference between tissue cohorts. Treatment did not influence miRNA expression in EV from Graves' disease tissue. Although miRNA-146a and -155 were elevated following treatment of non-Graves' disease tissue with dexamethasone and methimazole, the increase was not significant, likely due to small sample size. Conclusion: This preliminary study presents a unique method for isolation and characterisation of tissue specific EV for investigating disease pathogenesis and progression.